The digital economy and the quest for privacy protection in Bangladesh: a comparative legal analysis - Dhali, Mohsin; Zulhuda, Sonny; Ismail, Suzi Fadhilah (IIUM Press, 2020)
The present unbridled advancement in the field of information and communication technology has resulted in individuals being thrust at a crossroad, where refusing to sacrifice one’s privacy would mean the denial of technological benefits. Concern for privacy begins once a child is born into this world where the right to privacy could now be argued needs to be considered as one of the basic human rights similar to other inalienable rights such as the right to life and liberties. Bangladesh is one of the countries that has not given explicit recognition to the right of privacy. This is evident from the absence of explicit indications of the right to privacy in the Constitution of Bangladesh and judicial interventions make the constitutional protection of privacy questionable. The purpose of the present study is to find out whether the right to privacy is in fact recognized and protected by the Constitution of Bangladesh by examining specific provisions in the Constitution of Bangladesh to locate provisions that could be relied on to show that a sliver of recognition could be given to the right of privacy in Bangladesh. This position is then compared to other jurisdictions, especially the common law jurisdictions. The study finds that although Article 43 of the Constitution guarantees limited protection that encompasses the right to privacy of home and correspondence but if read together with the right to life and liberty in Article 32, it could be argued that these are viable provisions in recognizing the right to privacy under the Constitution of Bangladesh.